Mathematics in the streets and in schools - Pouya Karimi; Abolfazl Rafiepour (ریاضی و جامعه, 2025)
An analysis of everyday use of mathematics by working youngsters in commercial transactions in Recife, Brazil, revealed computational strategies different from those taught in schools. Performance on mathematical problems embedded in real-life contexts was superior to that on school-type word problems and context-free computational problems involving the same numbers and operations. Implications for education are examined.